Converting the Beef Cow Herd to a Controlled Breeding Season - Mario Binelli; Thiago Martins; Tim Wilson; Cindy Sanders; Mark Warren; Matt Hersom; Curt Lacy (EDIS)
This report aims to provide guidance to producers on practical aspects for moving from a system with no defined breeding season to a system with a defined season. Written by Mario Binelli, Thiago Martins, Tim Wilson, Cindy Sanders, Mark Warren, Matt Hersom, and Curt Lacy, and published by the UF/IFAS Department of Animal Sciences, revised January 2023.